1998
DOI: 10.1007/s002850050135
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Turing bifurcation using spatially varying diffusion coefficients

Abstract: Abstract. The Turing bifurcation is the basic bifurcation generating spatial pattern, and lies at the heart of almost all mathematical models for patterning in biology and chemistry. In this paper the authors determine the structure of this bifurcation for two coupled reaction diffusion equations on a two-dimensional square spatial domain when the diffusion coefficients have a small explicit variation in space across the domain. In the case of homogeneous diffusivities, the Turing bifurcation is highly degener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 29 publications
(32 reference statements)
1
54
0
Order By: Relevance
“…The Turing bifurcations for the Schnakenberg model with spatially varying diffusion coefficients are studied on a spatial two-dimensional square in [1]. It is shown how this spatial variation can be used to partially reduce the degeneracy in the Turing bifurcation.…”
Section: Previous Results On Peaked Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Turing bifurcations for the Schnakenberg model with spatially varying diffusion coefficients are studied on a spatial two-dimensional square in [1]. It is shown how this spatial variation can be used to partially reduce the degeneracy in the Turing bifurcation.…”
Section: Previous Results On Peaked Solutionsmentioning
confidence: 99%
“…To establish Part II, the analysis used in Part I is not good enough for the eigenvalues with λ = o (1) since knowing that their limit is zero does not tell us anything about the signs of the real parts of the eigenvalues for small. So a refined analysis is needed which goes beyond the leading order O(1).…”
Section: Previous Results On Peaked Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [34] similar results are shown for two-dimensional domains. In [2] it is shown how the degeneracy of the Turing bifurcation can be lifted using spatially varying diffusion coefficients. In [17,18,19] spikes are considered rigorously for the shadow system.…”
Section: A Cooperative Consumer Chain Modelmentioning
confidence: 99%
“…In particular, they found that if the parameter was chosen to be above its bifurcation value only in a sub-interval of the domain, then it was possible for patterns to propagate into the domain where linear analysis would predict stability of the uniform steady state-a situation they described as "environmental instability" (Benson et al, 1993). A detailed weakly nonlinear bifurcation analysis for the two-dimensional case showed how degenerate bifurcation points could be split using a spatially varying parameter (Benson et al, 1998). These results show that environmental inhomogeneity could be an important regulator of biological pattern formation.…”
Section: Previous Mathematical Modelsmentioning
confidence: 99%